Hyaluronic Acid in Bone Regeneration: Systematic Review and Meta-Analysis - Claudia Lorenzi; Andrea Leggeri; Ilaria Cammarota; Paolo Carosi; Vincenzo Mazzetti; Claudio Arcuri (MDPI AG, 2024)
Aim: The aim of this systematic review and meta-analysis was to assess possible histomorphometric differences in new bone formation and in remaining graft particles when hyaluronic acid (HA) was added and mixed with graft materials in bone regeneration. Materials and methods: This review was registered at the International Prospective Register of Systematic Reviews (PROSPERO) of the National Institute of Health Research (registration number CRD42024530030). Electronic research was performed, and involved studies published up to 29 February 2024 using a specific word combination. The primary outcome was to assess possible histomorphometric differences in new bone formation and in remaining graft particles when HA was added and mixed with graft materials in bone regeneration. The search resulted in 138 potential studies. Meta-analyses were performed using the fixed and random effects model to identify significant changes in new bone formation and in the remaining graft particles. Results: After screening procedures, only three randomized controlled trials fulfilled the inclusion criteria and were selected for qualitative and quantitative analysis. The effect size of HA in the new bone formation was not statistically significant at 95% CI (Z = 1.734, p-value = 0.083, 95 % CI -,399; 6516). The effect size of HA in the remaining graft particles was not statistically significant at 95% CI (Z = −1.042, p-value = 0.297, CI -,835; 255). Conclusions: Within the limitations of the present systematic review and meta-analysis, the addition of HA to bone graft did not result in significant changes in bone regeneration procedures in terms of new bone formation and residues, even if the included studies showed encouraging and promising results.